Duodenal Perforation with an Unusual Presentation: A Case Report - Arif Hussain Sarmast; Fazl Q. Parray; Hakim Irfan Showkat; Yasir A. Lone; Naseer A. Bhat (Case Reports in Infectious Diseases)
A young female presented with classical complaints suggestive of peptic ulcer disease leading to signs of peritonitis. The said patient after being subjected to baseline workup was subjected to laparotomy which proved to be a surgical surprise. A live ascaris lumbricoides worm was seen pouting out of a duodenal perforation.